CHARACTERIZATION OF ISOLATED CRYSTALS FROM MANGROVE LEAVES (AVICENNIA MARINA AND SONNERATIA ALBA) AND THEIR ANTIBACTERIAL ACTIVITY AGAINST STAPHYLOCOCCUS AUREUS - PERMATASARI, LINA; MULIASARI, HANDA; RAHMAN, FANIA (International Journal of Applied Pharmaceutics, 2024)
Objective: The study aimed to characterize the isolated crystal of Avicennia marina (A. marina) and Sonneratia alba (S. alba) leaves and identify the antibacterial activity of their isolated crystal. Methods: Each of the leaves A. marina and S. alba was extracted using ethanol 96%, then fractionated by liquid-liquid extraction method using n-hexane and ethyl acetate. The crystal of the isolated crystal was found in the water fraction. The isolated crystals were characterized using Fourier Transform-Infrared (FT-IR) and Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX) Spectroscopy and identified the antibacterial activity against Staphylococcus aureus (S. aureus) using the diffusion method. Results: The FT-IR spectrum showed that the isolated crystal was a polysaccharide structure with vibrations in the O-H, C=O, C-O, C-H, and S=O bonds. The SEM-EDX spectrum revealed the high-level content of carbon and oxygen, with sulfuryl group proposing the sulfated polysaccharide compound. Water fraction of A. marina and S. alba have inhibition zones 16 mm and 10 mm, respectively. The results showed the water fraction of A. marina and S. alba have strong and moderate antibacterial activity, respectively. Meanwhile, the antibacterial activity of the isolated crystal was none. The isolated crystal was estimated a sulfated polysaccharide but was not pure. So that the antibacterial activity was not detected. Conclusion: Even though, the water fraction of A. marina and S. alba leaves can be developed as antibacterial promising.